2011
DOI: 10.1159/000327023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Adiponectin and Aldosterone

Abstract: More than two thirds of the US population are considered overweight or obese. Adipocytes are now appreciated as important endocrine organs, secreting various factors with hormonal effects. Several different adipokines have been identified, including adiponectin, which is associated with improved insulin sensitivity, a better lipoprotein profile, and lower rates of vascular inflammation and cardiovascular disease. Several studies have identified the renin-angiotensinaldosterone system as important in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
(44 reference statements)
0
21
0
1
Order By: Relevance
“…It has been shown that aldosterone affects adiponectin and resistin secretion by adipose tissue [47][48][49]. Moreover, it is well known that progesterone is a natural antagonist of the mineralocorticoid receptor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that aldosterone affects adiponectin and resistin secretion by adipose tissue [47][48][49]. Moreover, it is well known that progesterone is a natural antagonist of the mineralocorticoid receptor.…”
Section: Discussionmentioning
confidence: 99%
“…It normally serves to reduce the expression of pro-inflammatory factors such as IL-6 and also affords anti-lipogenic protection to the cardiomyocyte mediated by AMPK (105). In addition, adiponectin may also be involved in aldosterone signaling in conditions of insulin resistance and diabetic heart disease (25). …”
Section: Development and Progression Of Cardiac Dysfunction As A Resumentioning
confidence: 99%
“…8 Adiponectin levels are inversely related to aldosterone (and sympathetic activity) levels. 9 Adipocytes and FFA Elevated FFA levels and uptake play an integral part in adipocyte physiology. They trigger increased pro-inflammatory expression via pathways that involve Toll-like receptor 4, nuclear factor kappa B (NF-jB), as well as several other mechanisms.…”
Section: A Primer On the Adipocytementioning
confidence: 99%